Russian aggression against Ukraine and international humanitarian law - Agnieszka SZPAK; Jakub KUFEL (Przegląd Geopolityczny)
The research aim of this paper is to examine the Russian aggression against Ukraine and the ensuing international armed conflict between these states in the light of international humanitarian law. The images of the destroyed cities of Mariupol, Irpin and Kharkov as well as the killings of civilians in Bucha shock the conscience of mankind and raise the question of their legal classification. The author answers the following questions: Which rules of international humanitarian law are being violated by Russia? Do these violations reach the level of international crimes such as war crimes, crimes against humanity or possibly genocide?